La cartographie héraldique de Frotier de la Messelière - Laurent Hablot (Les Cahiers de l'École du Louvre)
In 1960 Henri Frotier de la Messelière bequeathed 286 volumes of his notes and drawings on the monumental and heraldic heritage and the history of the department’s nobility to the Côtes-d’Armor archives. These include around fifteen maps showing the seats of the main seigneuries, together with the coats of arms of their holders. This “heraldic cartography” was a first, and we are delighted to offer a critical reading of it to highlight the potential of such a tool in the age of digital solutions.